Pengembangan Buku Cerita Bergambar Interaktif Berbasis Kearifan Lokal Suku Mbojo pada Mata Pelajaran IPAS Kelas III di SDN 2 Sila - Nurfitriah; Muhammad Tahir; Fitri Puji Astria (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science learning in elementary schools still faces various obstacles, especially in the use of learning media that are less interesting and have not integrated local culture in the learning process. As a result, students are less active, do not understand the material contextually, and have a low understanding of their own regional culture. This study aims to develop interactive picture storybook learning media based on local wisdom of the Mbojo tribe in science learning for grade III elementary schools that are valid and practical to use. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, linguists, teachers, and grade III students of SDN 2 Sila. The instruments used were validation questionnaires and practicality questionnaires. The results of the study showed that the level of media validity based on the assessment of material experts was 83.3%, linguists 86.3%, and media experts 93.75% with a very valid category. The results of the practicality test showed that student responses were 89.3% and teacher responses were 97.2% with a very practical category. Based on these results, interactive picture story books based on the local wisdom of the Mbojo tribe are suitable and practical for use in science learning.